Beyond Single-Pathogen Models: Understanding Mixed Infections Involving Phytoplasmas and Other Plant Pathogens - Shao-Shuai Yu; Wei Wei (Plants)
Phytoplasmas are wall-less, phloem-restricted bacteria responsible for numerous significant plant diseases worldwide. An increasing body of evidence indicates that phytoplasmas can coexist with other pathogens in mixed infections, including various 16Sr group phytoplasmas, ‘Candidatus Liberibacter’ species, viruses, spiroplasmas, fungi, and other difficult-to-culture phloem-limited bacteria. These interactions challenge established views regarding the causes, detection, and management of plant diseases. This review consolidates existing knowledge on the diversity and epidemiology of phytoplasma-related mixed infections, with a particular emphasis on documented co-infections across various host plants and regions, especially in tropical and subtropical areas. Mixed infections affect disease severity, symptom expression, vector behavior, and pathogen dissemination, highlighting the limitations of pathogen-specific diagnostic and control strategies. The necessity for tools to detect multiple pathogens, enhanced understanding of pathogen–pathogen and host–pathogen interactions, and comprehensive surveillance systems is emphasized. Ultimately, breeding for resistance must consider the complexities of natural co-infections to ensure effective protection of crops. Addressing the challenges presented by phytoplasma-related mixed infections is crucial for developing resilient and sustainable plant health strategies in the face of increasing ecological and agricultural pressures.